PENGUATAN KARAKTER KEPEMIMPINAN BERBASIS NILAI-NILAI AL QURAN DI SMP MUHAMMADIYAH 17 SURABAYA - Rusiyan; Tobroni; Faridi (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2025)
This study aims to examine the strengthening of leadership character based on the values ​​of the Qur'an as the main foundation in forming leaders who have integrity, morality, and a clear vision. The values ​​contained in the Qur'an, such as justice, wisdom, patience, trustworthiness, and empathy, have an important role in shaping the behavior and decisions of a leader. In this context, leaders are not only seen from the aspect of competence and technical skills alone, but also from the ability to lead with the principles established by Allah SWT. This study identifies various concepts of leadership in the Qur'an, relates them to modern leadership practices, and provides recommendations on how these values ​​can be applied in everyday life by leaders in various sectors. Thus, strengthening leadership character based on the Qur'an is expected to create leaders who are more ethical, responsible, and have a positive impact on society.